The Unified Conceptual Space Theory: an enactive theory of concepts. (June 2013) - Parthemore, Joel
Theories of concepts address systematically and productively structured thought. Until the Unified Conceptual Space Theory (UCST), based on Peter Gärdenfors' Conceptual Spaces Theory, no one had attempted to offer an explicitly enactive theory of concepts. UCST is set apart from its competitors in locating concepts not in the mind (or brain) of the conceptual agent nor in the affordances of the agent's environment but in the interaction between the two. On the UCST account, concepts are never truly static: conceptual knowledge is always in the process of being "brought forth", such that neither agent nor environment can cleanly be separated from the other, and the preconceptual noumena cannot be reconstructed free of conceptual taint. Through such conceptual coloring, mind extends into the world. Concepts create binary distinctions – beginning, most importantly, with the self/non-self distinction – and discrete entities that mask what are, with respect to the conceptual framework, underlying continua. These distinctions – implying notions of e.g. internal and external, inner experience and outer world – are both conceptually necessary and, at the same time, lacking prior ontological status. They are meaningful only with respect to some identifiable observer (which could, in appropriate circumstances, be the organism itself). In consequence, phenomenology has a key role to play, and first-person methods are indispensable to any empirical investigation of concepts.